Zastosowanie analizy korespondencji w badaniach związanych z motywami wyboru rodzajów wyjazdów turystycznych przez emerytów i rencistów w 2005 r. - Bąk, Iwona; Wawrzyniak, Katarzyna (The Use of Correspondence Analysis in Research Related to Motives of Choices of Departures Type by Pensioners and Annuitants in 2005, 2009)
The article is an attempt to answer the question about what factors have had an influence to decision taken by pensioners and annuitants about touristic departure. The research was made on the basis of the representative individual research of departures realized by pensioner and annuitants in 2005. Correspondence analysis was used as an investigate instrument. The results of research are presented in three-dimensional space. With regard to the big number of variants of analyzed variables, the Ward method was used which enables to assign the connection between variants of variables. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 324-332